Comparison of rabies virus protection by single chain and leucine zipper Fv fragments cocktail derived from a monoclonal antibody cocktail. (September 2018) - Xi, Hualong; Meng, Xiangyu; Gu, Tiejun; Li, Zhuang; Cheng, Yue; Sun, Qing; Zhang, Kaixin; Kong, Wei; Wu, Yongge
Highlights: Rabies is a global and fatal zoonotic disease with no known treatment. After rabies virus (RV) infection, vaccine and antibody administration is crucial. Developed single chain and leucine zipper Fv fragments cocktail (scFvs/zipFvs cocktail) against RV. Fragments showed efficient RV neutralization, with fast metabolism and low affinity. Optimized zipFvs may be promising substitutes for anti-RV antibodies. Abstract: Monoclonal antibodies (MAbs) are a unique and attractive class of biologics and are potential substitutes for post-exposure rabies prophylaxis. The safety, tolerance, and broad neutralization efficiency of a MAb cocktail called CL184, composed of the antibodies CR4098 and CR57, was confirmed in a phase I clinical trial. We have prepared a series of single-chain Fv fragments (scFvs) and leucine zipper Fv fragments (zipFvs) from CR57 and CR4098. In this study, we selected and formed scFv and zipFv cocktails and compared their protective effects against the rabies virus. Mice and hamster challenge models demonstrated the improved protection of the zipFv cocktail compared with scFv cocktail, because of its stronger affinity. The results indicate that zipFv production is a promising novel method for the genetic engineering of antibody fragments and improving affinity through systematic screening may be important when designing small molecule antibodies against RV.